A STUDY ON THE PRODUCTION OF A NEW MATERIAL FROM FLY-ASH AND POLYETHYLENE - ALKAN, C; ARSLAN, M; MEHMET, C; KAYA, M; AKSOY, M (Elsevier Science Bv, 1995)
Coal combustion fly ash is produced as a byproduct in huge amounts from pulverized coal-fired power plants. Waste plastics from packaging materials and other uses are recovered in large quantities. An investigation has been conducted to produce a new building material from fly ash and polyethylene. The work was carried out with two typical coal fly ashes and polyethylene bags. The tensile strengths and the chemical resistance of the materials, in addition to the effect of temperature were examined. Characterization of these materials was also studied by means of XRD, IR and SEM techniques. The tensile strengths of the materials range from 0.92 to 2.62 kp/mm(2). When the ratio of fly ash is low, better results were obtained. There was no significant loss in weight in solutions of NaOH (5%), CH3COOH (5%), C2H5OH (95%), H2SO4 (5%) and H2O.
Keywords: FLY ASH; POLYETHYLENE; BUILDING MATERIAL